Effects of slow internet on academic library staff productivity and job satisfaction - Oluwole O. Durodolu; Mercy A Iroaganachi; Josephine N Otunla (Berkala Ilmu Perpustakaan dan Informasi)
Introduction. This paper investigated the effects of slow internet on academic library staff productivity and job satisfaction of academic library staff using the University of Ibadan library as a case in focus.